Information Audit: Langkah Awal Menuju Layanan Prima pada Perpustakaan Badan Lit- bang dan Diklat Kementerian Agama - Hariyah Hariyah (Jurnal Adabiya, 2018)
Information audit provides a frame of checking for information activity to be created, collected, shared and saved. As that activity is being seen and proceed now and how it should be in the future where the changes from as is into as to be is expected to happen. The purpose of audit is to understand which information is needed to support institution’s activities, what kind of information do people use now, where do people gain information and is there a gap in accessing information. Audit may be used to analyze the information that people need, the resources that are being used to gain information and the challenges to access information. As a librarian it is important to give a service in accordance with the need of users and working in cooperation in organization to provide the needs of users. Information audit is one of the tools to improve the service for the users, and librarians should see this as an additional value from organization’s aspect activity.